THE INTERPRETATION OF THE HORSE AS A SYMBOL OF STRENGTH, FREEDOM, BEAUTY, AND DIGNITY IN TRANSLATION - Soibova Gulchiroy Baxtiyorjon qizi (Web of Journals Publishing, 2025)
This dissertation explores the symbolic image of the horse as reflected in English and Uzbek literary texts. It investigates the cultural values, metaphorical meanings, and emotional connotations associated with the horse in both cultures, revealing how this image reflects collective memory, worldview, and national identity. By analyzing original and translated literary texts, the research identifies key challenges in translating culturally loaded symbols and offers linguocultural strategies to preserve meaning, symbolism, and aesthetic impact. The study is grounded in modern approaches such as conceptual metaphor theory, pragmatics, and cross-cultural analysis, providing new insights into intercultural translation.
Keywords: Horse image, linguoculture, cultural symbolism, literary translation, metaphor, collective memory, national identity, conceptual metaphor, cross-cultural analysis.